Targeted nuclear antisense RNA mimics natural antisense-induced degradation of polyoma virus early RNA. - Liu, Z (1994)
We describe a general antisense strategy to inhibit target gene expression. The substitution of a cis-acting ribozyme for a polyadenylylation signal in an antisense expression vector results in the nuclear retention of RNAs and the efficient degradation of their targets. We demonstrate the utility of this system in polyoma virus, where early-strand RNA levels are downregulated in the nucleus by antisense late-strand counterparts. We show that mutations destabilizing these naturally occurring antisense transcripts lead to increased levels of early-strand RNAs. Furthermore, expression in trans of nuclear antisense transcripts lowers early-strand RNA levels and quantitatively mimics the natural regulation.